2022
DOI: 10.1093/ee/nvac005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synergistic Compounds on the Susceptibility of Euschistus heros (Hemiptera: Pentatomidae) and Chrysodeixis includens (Lepidoptera: Noctuidae) to Pyrethroids

Abstract: The Neotropical brown stink bug, Euschistus heros (F.), and the soybean looper, Chrysodeixis includens (Walker), are key pests of soybean in South America. Low susceptibility to pyrethroids has been reported for both species in Brazil. Here, we evaluate the addition of synergistic compounds piperonyl butoxide (PBO) and diethyl maleate (DEM) to manage E. heros and C. includens with resistance to λ-cyhalothrin and bifenthrin. The LD50 of technical grade and commercial products containing λ-cyhalothrin and bifent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…This is due to effects of synergistic compounds reducing physiological detoxification process by enzymes from cytochrome P450 monooxygenases, which are the major ones responsible for the resistance of this species to pyrethroids. 9,15 Similar detoxification mechanism was also reported in S. litura and S. exigua in which the synergist PBO reduced the resistance to deltamethrin 20,23 and in H. armigera and Plutella xylostella increasing its susceptibility to deltamethrin and fenvalerate. 22,49 The synergist DEM also enhanced the susceptibility of S. exigua and S. litura to cypermethrin and deltamethrin, respectively, revealing that the high expression of glutathione S-transferases enzymes are involved with the resistance mechanism.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This is due to effects of synergistic compounds reducing physiological detoxification process by enzymes from cytochrome P450 monooxygenases, which are the major ones responsible for the resistance of this species to pyrethroids. 9,15 Similar detoxification mechanism was also reported in S. litura and S. exigua in which the synergist PBO reduced the resistance to deltamethrin 20,23 and in H. armigera and Plutella xylostella increasing its susceptibility to deltamethrin and fenvalerate. 22,49 The synergist DEM also enhanced the susceptibility of S. exigua and S. litura to cypermethrin and deltamethrin, respectively, revealing that the high expression of glutathione S-transferases enzymes are involved with the resistance mechanism.…”
Section: Discussionsupporting
confidence: 72%
“…The high lethality can be explained by the reduction caused by synergists on the activity of detoxification enzymes including P450 monooxygenases and glutathione S‐transferases enzymes, confirming that these enzymes are mainly responsible for the metabolic detoxification of pyrethroids in E. heros from Brazil. Previous studies also demonstrated that the low susceptibility of this notorious soybean pest to BFT, LAM, methamidophos, endosulfan, and acephate was associated with high expression of α‐esterase, β‐esterase, and glutathione S‐transferases enzymes 13–15 . Similar resistance mechanism was reported in bed bugs of the genus Cimex (Hemiptera: Cimicidae), in which the detoxification of LAM and deltamethrin was associated with the overexpression of cytochrome P450 enzymes 47,48 .…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations